2022
DOI: 10.3390/life12020148
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intermittent Hypoxemia on Left Atrial Remodeling in Patients with Obstructive Sleep Apnea Syndrome

Abstract: Obstructive sleep apnea syndrome (OSAS) is a significant risk factor for left atrial (LA) remodeling. Intermittent hypoxemia occurs during the sleep cycle in patients with OSAS and plays a crucial role in cardiovascular pathologies such as stroke, arrhythmia, and coronary artery disease. However, there is very little information about the role of intermittent hypoxemia in LA remodeling in patients with OSAS. In total, 154 patients with sleep-related breathing disorders (SRBD) were prospectively recruited for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…The results of this study showed that peripheral blood TNF-α levels were significantly elevated in patients with ACI combined with OSAS and were positively correlated with the NIHSS and mRS scores, indicating that inflammation was aggravated by the occurrence of ACI and OSAS. In addition, intermittent hypoxia/reoxygenation (IHR) can also activate the TLR4/NF-κB signalling pathway, leading to inflammation and thus the upregulation of TNF-α, a downstream inflammatory factor [ 23 ]. TNF-α induces the expression of periostin through the transcription factor c-Jun [ 24 ], which is consistent with the results of the present study, in which Pearson correlation analysis showed that periostin was significantly positively correlated with TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that peripheral blood TNF-α levels were significantly elevated in patients with ACI combined with OSAS and were positively correlated with the NIHSS and mRS scores, indicating that inflammation was aggravated by the occurrence of ACI and OSAS. In addition, intermittent hypoxia/reoxygenation (IHR) can also activate the TLR4/NF-κB signalling pathway, leading to inflammation and thus the upregulation of TNF-α, a downstream inflammatory factor [ 23 ]. TNF-α induces the expression of periostin through the transcription factor c-Jun [ 24 ], which is consistent with the results of the present study, in which Pearson correlation analysis showed that periostin was significantly positively correlated with TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CIH drives an imbalance between collagen secretion and degradation. CIH may also contribute to atrial remodelling by promoting inflammatory myocardial apoptosis [ 69 , 78 ]. These processes are summarised in Figure 1 .…”
Section: Arrhythmogenic Mechanisms In Osamentioning
confidence: 99%
“…This implies a reactive oxygen species (ROS)-dependent remodelling process, either by direct protein oxidation or secondary cell signalling processes. Indeed, markers of oxidative stress are elevated in numerous OSA models [ 56 , 57 , 78 , 79 ]. This is a prominent feature of CIH, as ROS are cyclically produced with intermittent re-oxygenation in a fashion similar to ischaemia–reperfusion injury [ 81 ].…”
Section: Arrhythmogenic Mechanisms In Osamentioning
confidence: 99%
See 1 more Smart Citation
“…This pure or concentrated oxygen is indeed known as medical oxygen, and in the absence of it, a patient may experience hypoxemia [low levels of oxygenated blood ( 3 )]. Hypoxemia is caused by a range of common conditions—including childhood pneumonia, newborn conditions ( 4 , 5 ), and obstetric emergencies ( 6 , 7 ). The body of the sufferer will experience severe detrimental consequences from hypoxemia on the cells that carry out crucial biological functions ( 8 ).…”
Section: Introductionmentioning
confidence: 99%